2008
DOI: 10.1016/j.pcl.2007.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Palliative Care Practices into the Ongoing Care of Children with Cancer: Individualized Care Planning and Coordination

Abstract: Most parents of children with cancer have dual primary goals: a primary cancer-directed goal of cure and a primary comfort-related goal of lessening suffering. Early introduction of palliative care principles and practices into their child's treatment is respectful and supportive of these goals. The Individualized Care Planning and Coordination Model is designed to integrate palliative care principles and practices into the ongoing care of children with cancer. Application of the model helps clinicians to gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
112
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(118 citation statements)
references
References 76 publications
(13 reference statements)
0
112
0
6
Order By: Relevance
“…It aims to enhance communication about difficult issues by discerning patient and family values and priorities before critical decision points are reached. 23,24 This model is currently theoretical and is unproven in the research realm, but we have found it extremely useful in clinical practice.…”
Section: Figmentioning
confidence: 99%
“…It aims to enhance communication about difficult issues by discerning patient and family values and priorities before critical decision points are reached. 23,24 This model is currently theoretical and is unproven in the research realm, but we have found it extremely useful in clinical practice.…”
Section: Figmentioning
confidence: 99%
“…11 In short, it is evident that palliative interventions are necessary as suffering is universal for children with cancer and their families. 10 A further examination of definitional clarity, disease trajectory, and symptom management point out the unique obstacles facing PPC delivery in pediatric oncology.…”
Section: Pediatric Palliative Care In Oncologymentioning
confidence: 99%
“…10 Some known cancer-and treatment-related symptoms experienced in children with cancer include emesis, anemia, fatigue, distress, and pain. 10 These symptoms should be managed from diagnosis, supporting an integrative palliative and disease-directed approach to care; yet symptom management in pediatric oncology is not always successful.…”
Section: Pain and Symptom Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, however, there has been an increased appreciation for palliative care as an area of special need and expertise, but the breadth and integration of various specialty components remains variable [3]. This is compounded by the fragmentation of healthcare in the U.S. [4,5]. Implementation of palliative surgery, in particular, as an integrated component of palliative care remains a challenge.…”
mentioning
confidence: 99%